The learning of reading and writing in the inclusive perspective of vertical continuity. Down Syndrome, a case study in class - Francesca Salis (Firenze University Press, 2017)
For learning reading and writing skills it is considered essential to enhance the relational aspects among peers, inclusive and motivational ones, as intrinsic aspects to teaching methodology. During the transition from kindergarten to primary school it is advisable to take a vertical view, making it possible to treat a number of pre-skills such as visual-spatial and visual-perceptual ones, as well as phonological and metaphonological awareness, reading images and arranging picture stories in a ludic approach. Down syndrome, the most frequent cause of cognitive disability, though difficult to be diagnosed early and reliably, has a repertoire of consolidated educational practices that are well suited to transferability also to several cases of cognitive disabilities. Through the investigation of a class/section group making the transition from kindergarten to primary school, we will analyse the transversally distributed learning modes in the various areas of cognitive repertoire, in the belief that good reading and writing performances base processes that are fundamental to personal autonomy for all subsequent stages of existence.   L'apprendimento della lettura e scrittura nella prospettiva inclusiva della continuità verticale. Sindrome di Down, uno studio di caso in classe Per l'apprendimento delle abilità di letto-scrittura si considera fondamentale valorizzare gli aspetti relazionali tra pari, inclusivi e motivazionali, come aspetti intrinseci della metodologia didattica. Una prospettiva verticale, nel passaggio dalla scuola dell'infanzia alla primaria, consente di curare una serie di pre-abilità come quelle visuo-spaziali e visuo-percettive, la consapevolezza fonologica e metafonologica, la lettura di immagini e l'ordinamento di storie figurate presentate con approccio ludico. La sindrome di Down rappresenta la causa più frequente di disabilità cognitiva, di precoce e certa diagnosi e con un repertorio di consolidate prassi educative che ben si prestano alla trasferibilità anche in casi diversi di disabilità cognitiva. Attraverso l'indagine su un gruppo classe/sezione, che effettua il passaggio dalla scuola dell'infanzia alla scuola primaria, si analizzano le modalità apprenditive trasversalmente distribuite nei vari ambiti del repertorio cognitivo, nel convincimento che buone performances di lettura e scrittura contribuiscano a costruire processi di autonomia personale fondamentali per tutte le tappe esistenziali successive.